Socio-emotional readiness and classroom ecology in 5th-grade EFL classrooms: a responsive evaluation of the English curriculum in Türkiye - Kuzu, Hateme Aysel; Egmır, Eray (Frontiers in Psychology, 2026)
IntroductionThis study examines the socio-emotional and interactional dynamics shaping young learners’ engagement with the 5th-grade English curriculum in public secondary school contexts in Türkiye. Drawing on a responsive curriculum evaluation approach and grounded in classroom ecology and socio-cultural learning perspectives, the study focuses on how socio-emotional readiness, instructional mediation, and contextual demands shape communicative language learning.MethodsA qualitative case study design was employed. Data sources included curriculum document and textbook analysis, classroom observations, semi-structured interviews with seven English teachers, one teacher focus group, and a separate focus group with seven 5th-grade students. Data were analyzed using inductive thematic analysis.ResultsFindings indicate that students’ participation in spoken English activities was closely associated with emotional security, peer-related evaluative concerns, and a sense of classroom belonging. Teachers reported experiencing significant pressures related to curriculum pacing and assessment expectations, which constrained opportunities for communicative interaction and intensified emotional labor. The analysis also revealed context-bound misalignments between intended communicative outcomes and enacted classroom practices, shaped by limited instructional time and the emphasis of instructional materials on vocabulary recall rather than contextualized use.DiscussionThe findings highlight the importance of attending to emotional safety, interactional support, equitable material conditions, and adaptive instructional pacing within specific classroom contexts. From a responsive evaluation perspective, the study demonstrates how socio-emotional and ecological constraints influencing curriculum enactment can be made visible beyond outcome-based indicators, offering implications for curriculum support, teacher development, and communicative language pedagogy.